Challenges and effective strategies for developing and scaling solutions to reduce food loss and waste in Kenya’s fruit and vegetable sector - Owino, Willis O.; Kahenya, Peter; Wafula, Elizabeth; Otieno, Geoffrey (Frontiers in Horticulture, 2024)
The sustainability of fresh fruits and vegetables value chains is challenged by high levels of food loss and waste (FLW) in resource-limited economies. In Kenya, where smallholder farmers dominate the food production sector, FLW in fruits and vegetables is estimated at 30-40%. This study investigated the ecosystem of FLW solution providers in Kenya, examining the challenges faced in developing and scaling interventions, and identifying successful strategies to overcome these barriers. A qualitative approach was employed. Primary data on FLW was obtained from solution providers through key informant interviews. The FLW solution providers were categorized as either successful or partially successful based on their commercial viability and operational tenure. The study utilized purposive sampling and a structured interview guide. The study identified several key challenges faced by FLW solution providers which comprised insufficient technical knowledge in food processing and machine operation, limited financial capacity for both operation and scaling, inconsistent supply of raw materials due to seasonality, competition from established companies and artificial products, slow market penetration, and low product acceptability (for partially successful providers). Successful solution providers employed various strategies to overcome these challenges including partnering with universities, governmental and non-governmental organizations for research, development, and initial financing; undertaking comprehensive technical and commercial viability assessments before scaling; adopting product differentiation to capture diverse markets; utilizing preservation techniques like drying and establishing off-take contracts to counter supply inconsistencies and establishing stable external markets and reliable business to business models. The study also revealed the potential for gender-inclusive impact, as many solution providers tend to employ more women due to the nature of the work. The findings highlight the critical role of partnerships, comprehensive market research, and adaptive strategies in developing successful FLW solutions. The contrast between successful and partially successful solution providers underscores the importance of comprehensive planning, technical expertise, and market-oriented approaches. By learning from successful solution providers and addressing key challenges, stakeholders can create more sustainable and effective interventions to reduce FLW and improve food security and nutrition status, and enhance the livelihoods of smallholder farmers.